Analyzing the Impacts of Restructuring on the Turkish State-Owned Banks - SARISAKALOGLU, Gazi; BILGIN, Mustafa (Journal of Economic Development, Environment and People, 2017)
The subject of this research is to compare the performance based on determined criteria of the state owned banks in Turkey before 10 years and after 14 years from 2001 the date they were included in a restructure program. The t-test method is used in the study. According to the results of the analysis, it was concluded that the most successful state-owned bank was Halkbank with a small margin in front of Ziraat Bank after the year that the restructuring program was implemented. Ziraat Bank, as well as having the second most positive development of public banks in terms of analysis ratios, it has almost equal proportions with Halkbank in terms of asset quality and branch ratios. Halkbank is ranked first as usual in terms of branch ratios. All state owned banks are subject to the close rates for branch ratios. When evaluating the performance of public banks in general over a total of 36 criteria, they showed positive development for 26 criteria. That means after the restructuring program that we called 2nd period in the study public banks became more successful based on established criteria.